Poisoning by plants, mycotoxins, and related toxins - Riet-Correa, Franklin (CABI, 2011)
A collection of up-to-the-minute research in the field of poisonous plants that investigates the effects of toxins on animals and humans. It covers the effects of poisonous plants on the liver, the reproductive system, and the nervous system, as well as exploring the field of herbal medicine